Analisis Putusan Mahkamah Internasional dalam Kasus Sengketa Indonesia-Malaysia Mengenai Pulau Sipadan dan Ligitan (Universitas Negeri Semarang, 2021)
Disputes between Indonesia and Malaysia in the International Court of Justice on the issues of the islands of Sipadan and Ligitan continued to roll throughout the year until 1997 both countries raised this issue in international law. The two islands which are located in the center of Indonesia, precisely in the Makassar Strait, were finally won by the Malaysian side on December 17, 2002 The Court finally decided that Malaysia is the party that has full sovereignty over Sipadan Island and Ligitan Island. In its decision. The court made the doctrine of